(E)-1-(4-Hydroxyphenyl)-3-(substituted-phenyl) prop-2-en-1-ones: Synthesis, in Vitro Cytotoxic Activity and Molecular Docking Studies - GÖRGÜLÜ, AHMET ORHAN (My University, 2022)
© 2022 Slovensko Kemijsko Drustvo. All rights reserved.A series of chalcone compounds (2–11) were designed and synthesized to determine their cytotoxic effects. The structures of 2–11 were fully characterized by their physical and spectral data. The in vitro cytotoxic effects of 2–11 were evaluated against human ovarian cancer (A2780), breast cancer (MCF-7) and prostate cancer (PC-3 and LNCaP) cell lines. The activity potentials of compounds were further evaluated through molecular docking studies with AutoDock4 and Vina softwares. All the compounds (except compound 5) showed significant cytotoxic effects at high doses in all cancer cell lines. Among all the compounds studied, one compound i.e. compound 2 demonstrated dose-dependent activity, particularly against A2780/LNCaP cancer cell lines. The most effective compounds 8, 9, 10 and 11 reduced the cell viability of A2780, MCF-7, PC-3 and LNCaP cells by 50–98%, while other compounds 2, 4 and 7 reduced the cell viability of A2780 cells by 70–90% at concentrations of 50 and 100 µM.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; A2780; Chalcone; cytotoxic; molecular docking; MTT assay